Peran KH. Zafry Zamzam dalam Dunia Pendidikan Islam di Kalimantan Selatan - Viryanti, Novi; Jamalie, Zulfa (Pascasarjana UIN ANTASARI Banjarmasin, 2023)
KH. Zafry Zamzam, a teacher, lecturer, official, journalist and preacher, had a strong vision and mission for quality education based on religious values. He contributed to the development of formal and non-formal education in the area, including establishing religious schools, colleges and playing an important role as Rector of IAIN Antasari Banjarmasin (now UIN). His achievements and work reflect his love of country and high fighting spirit. The main impact of his contributions was the spread of religious values, the spirit of independence, and spreading knowledge to the community through various means including mass media, social organizations, and religious education. This research uses descriptive analytical method to analyze KH. Zafry Zamzam's role in developing Islamic education in South Kalimantan, his contribution in leading educational, political and journalist institutions and his impact on society and education in the area.